The impact of entrepreneurship on economic, social and environmental welfare and its determinants: a systematic review - Thomas Neumann (Management Review Quarterly, 2020)
This paper presents a systematic review of (a) the impact of entrepreneurship on economic, social and environmental welfare and (b) the factors determining this impact. Research over the past 25~years shows that entrepreneurship is one cause of macroeconomic development, but that the relationship between entrepreneurship and welfare is very complex. The literature emphasizes that the generally positive impact of entrepreneurship depends on a variety of associated determinants which affect the degree of this impact. This paper seeks to contribute to the literature in three ways. First, it updates and extends existing literature reviews with the recently emerged research stream on developing countries, and incorporates studies analysing not only the impact of entrepreneurship on economic growth and welfare but also on social and environmental welfare. Second, it identifies and structures the current knowledge on the determinants of this impact. And third, it provides a roadmap for future research which targets the shortcomings of the existing empirical literature on this topic. The review of 102 publications reveals that the literature generally lacks research which (a) goes beyond the common measures of economic welfare, (b) examines the long-term impact of entrepreneurship and (c) focuses on emerging and developing countries. Regarding the determinants of the impact of entrepreneurship, the results highlight the need for empirical research which addresses both already investigated determinants which require more attention (e.g. survival, internationalisation, qualifications) and those which are currently only suspected of shaping the impact of entrepreneurship (e.g. firm performance, the entrepreneur's socio-cultural background and motivations).
Keywords: A12; B55; L26; M13; O40; 650; Entrepreneurship; Startup; Employment; Economic development; Sustainable development; Developing countries